Standardized measurement of dielectric materials’ intrinsic triboelectric charge density through the suppression of air breakdown - Liu, Di; Zhou, Linglin; Cui, Shengnan; Gao, Yikui; Li, Shaoxin; Zhao, Zhihao; Yi, Zhiying; Zou, Haiyang; Fan, Youjun; Wang, Jie; Wang, Zhong Lin (Nature communications, 2022)
Triboelectric charge density and energy density are two crucial factors to assess the output capability of dielectric materials in a triboelectric nanogenerator (TENG). However, they are commonly limited by the breakdown effect, structural parameters, and environmental factors, failing to reflect the intrinsic triboelectric behavior of these materials. Moreover, a standardized strategy for quantifying their maximum values is needed. Here, by circumventing these limitations, we propose a standardized strategy employing a contact-separation TENG for assessing a dielectric material’s maximum triboelectric charge and energy densities based on both theoretical analyses and experimental results. We find that a material’s vacuum triboelectric charge density can be far higher than previously reported values, reaching a record-high of 1250 µC m −2 between polyvinyl chloride and copper. More importantly, the obtained values for a dielectric material through this method represent its intrinsic properties and correlates with its work function. This study provides a fundamental methodology for quantifying the triboelectric capability of dielectric materials and further highlights TENG’s promising applications for energy harvesting. Determining the triboelectric charge and energy density of dielectric materials is generally limited by many factors, failing to reflect their intrinsic behaviour. Here, a standardized strategy is proposed employing contact-separation TENG and supressing air-breakdown to assess max triboelectric charge and energy densities leading to an updated triboelectric series.